Proceedings of the 4th Asia Pacific Education Conference (AECON 2017) 2017
DOI: 10.2991/aecon-17.2017.24
|View full text |Cite
|
Sign up to set email alerts
|

Improving Student's Listening Skill Using Task- Based Approach in EFL Classroom Setting

Abstract: Abstract-This research aimed to investigate the improvement of the students" listening skill by using Task-Based learning Approach at higher school of foreign language Teknokrat in Lampung Province. To reach the goal, the research was conducted in two cycles; each cycle consists of three meetings. A number of research subjects were 35 students in the first semester majoring English literature in the 2016/2017 academic year. The instruments were observation, test, and questionnaire. The research findings showed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 5 publications
0
9
0
Order By: Relevance
“…The third example is research done by Kuswoyo and Wahyudin (2017). The study is designed to answer the following question: What is the students' perception of task-based learning and whether listening skills increase with taskbased learning?…”
Section: Example Of Classroom Action Researchmentioning
confidence: 99%
“…The third example is research done by Kuswoyo and Wahyudin (2017). The study is designed to answer the following question: What is the students' perception of task-based learning and whether listening skills increase with taskbased learning?…”
Section: Example Of Classroom Action Researchmentioning
confidence: 99%
“…Generally, English is widely used by many people and many countries for various purposes in the world. One of them is as a purpose of communication (Eng, Luyue, & Lim, 2020;Kuswoyo & Susardi, 2017;Hervina, 2014;Kuswoyo &Wahyudin, 2017). Further, some studies have found that as an international language, English becomes a compulsory subject that must be learned from school to university contexts (Asih, Asrianto, & Murwantoro, 2020; (Eng, Luyue, & Lim, 2020) A large and growing body of literature has investigated the main goal of learning English as a foreign and second language is a communicative competence (Phettongkam, 2017;Ruminar, 2018;Simbolon, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, Nunan (2013) also said that "Speaking is one of the important and essential skills that must practice communicating orally, and it is a priority for many second and foreign language learners." By seeing that importance, teachers have to find a way in teaching oral communication and pay attention to some factors such as tasks given (Kuswoyo and Wahyudin, 2017) and characteristics and learning styles (Wahyudin and Rido, 2020) of their students. It is in line with Oktaviani (2016) that the speaking skills of EFL students influenced by some factors.…”
Section: Introductionmentioning
confidence: 99%